Polymer brushes based on PLLA-b-PEO colloids for the preparation of protein resistant PLA surfaces - Mázl Chánová, E; Pop-Georgievski, O; Kumorek, M M; Janoušková, O; Machová, L; Kubies, D; Rypáček, F (Biomaterials science, 2017)
In this study we investigate the formation of protein-resistant polymer surfaces, such as aliphatic polyesters, through the deposition of self-assemblies of amphiphilic poly(l-lactide)-b-poly(ethylene oxide), PLLA-b-PEO, copolymers as stable nanoparticles with a kinetically frozen PLLA core on model PLLA surfaces. The length of the PEO chains in the corona was tuned to achieve polymer brushes capable of preventing protein adsorption on PLA-based biomaterials. The spectroscopic ellipsometry, IR and XPS analysis, contact angle goniometry, and AFM proved that the PEO chains adopted a brush structure and were preferably exposed on the surface. The low-fouling properties of the physisorbed PLLA-b-PEO layers approached the ones of reactive grafting methods, as shown by surface plasmon resonance spectroscopy. The anti-fouling properties of the prepared PEO brushes provided sufficient interface to prevent cell adhesion as proved in vitro. Thus, the developed surface coating with PLLA-b-PEO colloids can provide an anti-fouling background for the creation of nanopatterned biofunctionalized surfaces in biomedical applications.
Keywords: Biocompatible Materials; Colloids; nádorové buněčné linie; adsorpce; Cell Adhesion; Nanoparticles; proteiny; endoteliální buňky pupečníkové žíly (lidské); povrchové vlastnosti; biokompatibilní materiály; polyestery; Cell Line, Tumor; Polyethylene Glycols; koloidy; polyethylenglykoly; Surface Properties; Humans; Proteins; nanočástice; Polyesters; buněčná adheze; Human Umbilical Vein Endothelial Cells; Adsorption; lidé